Pengaruh Persepsi Mengenai Profesi Akuntan Publik, Motivasi, dan Kecerdasan Adversity Terhadap Minat Menjadi Akuntan Publik - Paramita S, Putu Vicky Yuliana; Mediatrix Ratna Sari, Maria (E-Jurnal Akuntansi; Vol 26 No 1 (2019), 2019)
Public accountants play a role in improving the quality and credibility of financial information. The interest of the people to become a public accountant, is still low. This study aims to determine the interest of non-regular accounting students to become public accountants as measured by student perceptions, self-motivation, and adversity intelligence. This research was conducted on 2015 non-regular accounting students at the Faculty of Economics and Business at Udayana University. Determination of samples using non-probability sampling method with saturated sampling technique. The number of respondents used in this study was 158 people. Data collection method is carried out by a survey method with questionnaire techniques that are measured using a Likert scale. The results of this study indicate that the variables of student perception, self motivation, and adversity intelligence have a positive influence on the interest of non-regular accounting students at Udayana University to become public accountants. Keywords:  student perception, self motivation, adversity intelligence, interest in becoming a public accountant.